Amicalement vôtre. - Brochard, Yves; Goudinoux, Véronique; Decaux, Mathilde; Graftieaux, Marie; Musée des Beaux-Arts, Tourcoing (Lille : Les artistes et les auteurs, 2004)
Gerstner, Karl ; Roth, Dieter ; Spoerri, Daniel ; Thomkins, André ; Arthuis, Isabelle ; Barry, Orla ; Benault, Stéphane ; Bertrand, Corinne ; Boucher, Caroline ; Braeckman, Dirk et al.
Amicalement vôtre, Musée des Beaux-Arts, Tourcoing, Mars-Mai 2004
kunstcatalogus